Media campaigns, evolution and concept - Jaeed , Hameed (ALBAHITH ALALAMI, 2005)
In dealing with media management phenomenon, concept and elements, we have tried, as much as possible, to build an abstract concept that can be analyzed and measured by analyzing the elements and components of the concept mentioned and explain it.Before further consideration of the management of media campaigns, it is necessary to restore some points of media management so as not to understand the subject of campaign management as if it is independent of the concept of media management and the objectives that we seek to ensure its achievement. As we have noted that the concept of media management frames the administration mentioned as:- Authority to manage the media institution.- Operations supervised by the mentioned authority.- Aim to be achieved by the authority concerned.- The purpose of the authority (Media Department).- Means used by the authority (Media Department) to carry out its functions or jobs assigned to it. If we compare the nature of media management to the nature of media campaign management, perhaps we do not find any boundaries between the two, the second - the campaign management - is an extension of the first, if not a reflection of its contents.More precisely, one of the most important justifications for resorting to campaign management is because it is an extension of the logic, meaning and content of the media administration.It is one of the most important aspects of media management during crises facing media institutions and their operations for national, environmental, institutional, health or cultural reasons. In other words, if the purpose of media campaigns is to overcome and address the crises faced by the media organizations and their repeated operations, then the need arises in return for the necessity to double media effort.In other words, if the purpose of the media campaigns is to overcome and address the crises faced by the media institutions and their repeated operations, then the need arises in return for the necessity to redouble the media effort in order to disseminate information or develop national awareness on specific topics. As well as, the focus of media activities in order to overcome the hierarchical crises that appear from time to time. From here we can indicate the relationship between the two departments, especially if we know that the media administration loses some of its features when dealing with media campaigns. A non-expanded campaign is usually targeted, location and time-bound.